Hyperinflammatory syndrome resembling haemophagocytic lymphohistiocytosis following axicabtagene ciloleucel and brexucabtagene autoleucel. (16th September 2022) - Porter, Timothy J.; Lazarevic, Ana; Ziggas, Jamie E.; Fuchs, Ephraim; Kim, Kiryoung; Byrnes, Helen; Luznik, Leo; Bolaños‐Meade, Javier; Ali, Syed Abbas; Shah, Nirali N.; Wagner‐Johnston, Nina; Jain, Tania
Summary: Haemophagocytic lymphohistiocytosis‐like toxicity following chimeric antigen receptor T cells (CAR‐HLH) is being increasingly recognized, while published data are limited and criteria for recognition are elusive. We describe three patients who developed CAR‐HLH after infusion of brexucabtagene autoleucel ( n = 2) or axicabtagene ciloleucel ( n = 1). All three patients presented following cytokine release syndrome, with fever, recurrent or worsening cytopenias, hyperferritinaemia, elevated soluble interleukin (IL)‐2 receptor, hypofibrinogenaemia, hypertriglyceridaemia, elevated liver transaminases, and decreasing C‐reactive protein and IL‐6. Clinical improvement following treatment with anakinra ( n = 2) and ruxolitinib ( n = 1) was observed. Our report offers an opportunity for prompt recognition and initiation of potentially life‐saving treatment for CAR‐HLH.